(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Rhizophora stylosa is a type of mangrove used for various purposes, including as a source of charcoal and firewood. This type of mangrove is also used in traditional medicines for mangosteen, wounds, toothache, lucid, liver, and itching. It is possible because these species contain secondary metabolites (bioactive). This study aimed to identify secondary metabolites from the root extract of Rhizophora stylosa accession from Morotai Island. Root samples of R. stylosa were obtained from Pandanga Village, South Morotai, Morotai Island. Extraction by maceration using methanol. Secondary metabolites are identified qualitatively, including alkaloids, saponins, flavonoids, triterpenoids, and steroids. The yield of the methanol extract of Rhizophora stylosa root was determined to be 26.42%, with a dry paste-like consistency. Alkaloids and saponins were the secondary metabolite compounds identified in the extract.